Galactic Gamma-Ray Diffuse Emission at TeV Energies with HAWC Data - R. Alfaro; C. Alvarez; J. C. Arteaga-Velázquez; K. P. Arunbabu; D. Avila Rojas; R. Babu; V. Baghmanyan; E. Belmont-Moreno; C. Brisbois; K. S. Caballero-Mora; T. Capistrán; A. Carramiñana; et al. (The Astrophysical Journal, 2024)
Galactic gamma-ray diffuse emission (GDE) is emitted by cosmic rays (CRs), ultra-relativistic protons, and electrons, interacting with gas and electromagnetic radiation fields in the interstellar medium. Here we present the analysis of teraelectronvolt diffuse emission from a region of the Galactic plane over the range in longitude of l ∈ [43°, 73°], using data collected with the High Altitude Water Cherenkov (HAWC) detector. Spectral, longitudinal, and latitudinal distributions of the teraelectronvolt diffuse emission are shown. The radiation spectrum is compatible with the spectrum of the emission arising from a CR population with an index similar to that of the observed CRs. When comparing with the DRAGON base model , the HAWC GDE flux is higher by about a factor of 2. Unresolved sources such as pulsar wind nebulae and teraelectronvolt halos could explain the excess emission. Finally, deviations of the Galactic CR flux from the locally measured CR flux may additionally explain the difference between the predicted and measured diffuse fluxes.